Evaluation of Rural Urban Waste Management : Integrating Logic Model and GIS Approach in Pemalang, Central Java, Indonesia - Mansur Hidayat; Maryono Maryono; Widjonarko Widjonarko; Muhammad Dzaky Taqyuddin; Padmagitaning Saraswati (Jurnal Ilmu Lingkungan, 2024)
To carry out the mandate of Presidential Regulation Number 97 of 2017 concerning Household Waste Management Policies and Strategies, the Pemalang Regency Government issued Regent Regulation Number 60 of 2018. This policy consists of 2 (two) main programs, namely the waste reduction program with a target of 30% and waste treatment, with a target 70%. This study aims to evaluate the program. The methods used are logic model and GIS. Logic models evaluate input process output and program outcomes, while GIS evaluates geospatial program achievements. Total of 8 indicators were evaluated, consisting of 3 (three) indicators for the reduction program and 5(five) indicators for the treatment program. For waste reduction program, 3 (three) indicators that are assessed, namely 1) Development of waste banks; 2) Development of compost houses and 3) development of TPS3R. In handling, 5 (five) indicators were analyzed, namely 1). Sorting; 2) Collection; 3) Transportation; 4) Itermediate Treatment; 5). Final treatment. Assessment for 2 years (2021-2023) shows 1). The number of waste banks increased by 32 units from 63 to 95 units; 2) Composting facilities increased by 2 units from 1 to 3) TPS3R facilities increased by 3 units from 3 to 6. GIS analysis showt that waste reduction programs are implemented mostly in urban areas. For treatment program, 84.92% of waste has been handled while 15.08% has not yet. The number of TPS for collection increased by 18 units from 116 units, to 134 units. There have been no significant changes regarding sorting and transportation and Intermediate treatment. In 2023, a landfill fire occurred, indicating that the final processing facilities were not yet optimal.